Dialogue with Raven:: Bakhtinian Theory and Lee Maracle’s Ravensong - Dadey, Bruce (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Bakhtinian theory, with its emphasis on dialogism, has been a particularly productive tool for analyzing and understanding literatures that draw on oral traditions. Lee Maracle's Ravensong raises the question of how, in a colonial context, cultural dialogue is possible on two different levels: within the story of the novel (diegetically) as it depicts the struggles of Stacey, a young Salish woman, and outside the story of the novel (extradiegetically) in the discursive strategies used to tell the story. The idea of dialogue is therefore both effected and interrogated; the work accommodates and yet resists Bakhtin's ideas as it reveals the complex dynamics of dialogue when interlocutors are separated by a cultural, social, and economic divide.